Control of type 2 diabetes in King Abdulaziz Housing City (Iskan) population, Saudi Arabia - Thamer A Alsulaiman; Hejab A Al-Ajmi; Saeed M Al-Qahtani; Intisar M Fadlallah; Nashwa E Nawar; Reem E Shukerallah; Sadaf R Nadeem; Nora M Al-weheedy; Khalid A Al-sulaiman; Adel A Hassan; Ayman A Shahin; Tamer M Kolib (Wolters Kluwer Medknow Publications, 2016)
Objective: To assess the level of control and prevalence of type 2 diabetes in King Abdulaziz Housing City (Iskan) population of Saudi Arabia. Materials and Methods: Retrospective cross-sectional study conducted in a primary-care setting. All Type 2 diabetics referred to our diabetes center between January 2011 and January 2015 were identified, and their computerized records reviewed. Glycated hemoglobin levels (HbA1c), low-density lipoprotein (LDL), blood pressure (BP), and the albumin-creatinine ratio (ACR) were noted and the patients categorized accordingly. Demographic data (age and gender) were also documented. Inactive patients (not seen for more than 2 years) were excluded. Results: The overall prevalence of type 2 diabetes for all age groups in ISKAN population was 3.25%. About 56% of the diabetics were female and 70% were aged between 18 and 59 years. The rate of uncontrolled diabetes was 59.3%. Males were more likely to have uncontrolled diabetes (odds ratio: 1.44, CI: 1.17-1.76, P = 0.0004). Forty percent of the diabetics had an LDL above target (≥2.6 mmol/l) while 25.9% had uncontrolled hypertension (BP ≥ 140/90 mmHg). Of those who had an ACR test done within the last year (59.3%), the rate of micro- and macro-albuminuria was 8.8% and 2.5%, respectively. Conclusions: The overall prevalence of type 2 diabetes in our community seems lower than the previously reported national figures. An alarming number of diabetics in our population have an uncontrolled disease. More stringent diabetes annual review and recall program is needed to control diabetes and reduce complications.